Answer:
$29
Explanation:
By running through the question we find,
i. Jim = Brother/2
ii. Jim = Sister - 27
iii. Jim = Jim + 12
iv. Sister = Sister + 12
v. Brother - 24 = Sister + 12/2
/////////////////////////////////////////////////////////////////////////////
By looking at above equations we know that,
Jim = Sister - 27
/////////////////////////////////////////////////////////////
where from equation iii and iv, Jim = Jim + 12 and Sister = Sister + 12
Jim + 12 = Sister + 12 - 27
/////////////////////////////////////////////////////////////
where, from equation v, Brother - 24 = Sister + 12/2 => Sister + 12 = 2(Brother - 24)
Jim + 12 = 2(Brother -24) - 27
/////////////////////////////////////////////////////////////
where from equation i, Jim = Brother/2 => Brother = 2*Jim
Jim + 12 = 2(2*Jim - 24) - 27
/////////////////////////////////////////////////////////////////////////////
Hence,
Jim + 12 = 4*Jim - 48 - 27
Jim + 12 = 4*Jim - 75
Jim - 4*Jim + 12 = -75
Jim - 4*Jim = -75 - 12
Jim(1 - 4) = -87
Jim(-3) = -87
Jim = -87/-3
Jim = 29